Being Old Does Not Mean “All the Same”: - Yuriko Isoda; Rei Kudo; Naoto Onzo (Maketingu Janaru)
It has occurred to marketers that the senior market is not a single homogeneous segment but a diverse group of consumers, and that marketing strategies should be tailored to this diversity. However, existing research has not provided sufficient frameworks for capturing heterogeneity among the senior market. In this study, we used future time perspective (FTP) and future self-continuity (FSC) as indicators of diversity in the senior market and conducted an exploratory survey among senior women. The results showed that FTP had a negative effect on purchasing activity for non-consumable goods, whereas FSC had a positive effect. An interaction was also observed between FTP and FSC, indicating that the most active consumers were “senior women who have a strong connection with their future selves but feel that their remaining time is not long.” In contrast, “senior women who have a strong connection with their future selves and feel that their remaining time is long” tended to refrain from financial expenditures on the aforementioned goods.